Phase precipitation behavior of rapidly quenched ternary La–Fe–B alloy and the effects of Nd substitution. (2nd August 2017) - Zhang, Z Y; Zhao, L Z; Zhang, J S; Zhong, X C; Qiu, W Q; Jiao, D L; Liu, Z W
Abstract: To understand the structure and phase precipitation behavior of the ternary La–Fe–B alloy, the effects of wheel speed and heat treatment on the melt spun La2 Fe14 B alloy were investigated. The results show that the hard magnetic La2 Fe14 B (2:14:1) phase is difficult to obtain in the ternary alloy. The α -Fe and La phases mainly precipitated as spun ribbons prepared at relatively low wheel speeds, and a more amorphous phase formed at higher wheel speeds. With the annealing temperature increasing from 400 °C to 500 °C and 800 °C, the α -Fe and La phases also gradually precipitated from the amorphous matrix. A liquid La-rich phase and α -Fe phase could coexist in the alloy at high temperature. However, the substitution of Nd for La can greatly enhance the formation of a hard 2:14:1 phase. The effects of Nd substitution on the structure and phase precipitation during annealing for the (La1− x Nd x )2 Fe14 B ( x   =  0.1. 0.2, 0.3 and 0.4) alloys have been also investigated. The present results are important for exploring high-performance low-cost La-based Nd–Fe–B magnets.